Analytical model of subthreshold drain current for nanoscale negative capacitance junctionless FinFET. (March 2022) - Kaushal, Shelja; Rana, Ashwani K.
Abstract: In this article, an analytical Subthreshold Drain Current model has been developed for Negative Capacitance Junctionless FinFET (NC-JL FinFET). To obtain the subthreshold current model for NC-JL FinFET the drift-diffusion equation is solved by including negative capacitance effect through LK equation and further utilized to attain the expression of subthreshold slope (SS). The influence of the fringing field due to source/drain spacer on the subthreshold current has been included in the model. The model predictions turn out to be in fair agreement with numerical simulation results. The performance of NC-JL FinFET is also examined for different technology nodes. Also, the influence of physical parameters like ferroelectric thickness, gate dielectric constant, fin thickness, spacer length etc. has also been analyzed. Further, the SS is also examined for variations in several device design parameters. It has been revealed that the NC-JL FinFET improves subthreshold current and SS by almost 80% and 16.7%, respectively as compared to JL FinFET. Highlights: Analytical model for Isub and SS of NC-JL FinFET has been developed. Effect of fringing field lines are also taken into consideration. NC-JL FinFET shown 80% improvement in Isub than JL FinFET. It also provides 16.7% steeper slope as compared to JL FinFET. It offers much better gate control with thinner TSi and thick TFE .